Domains of Safety - Jerzy M. Wolanin (Communications - Scientific letters of the University of Zilina, 2006)
It is considered that providing safety in universal dimension is exclusively responsibility of a public authority and the authority is fully responsible for efficient implementation of systems concerned with it. In reality, there is no prospect of not having incidents and therefore, there is no absolute safety. If such ideas exist anywhere, they are only theoretical concepts. Safety is a condition of the surroundings and natural environment of a local community. The condition level is defined by the degree of existing risk in that community. The risk is ubiquitous and inevitable as it exists in nature and civilian space. So the local governing body must decide what level of risk it is able to accept.Safety includes a wide range of undertakings be realized in order to provide security in all areas of concern in the state. Therefore, safety is the result of activities of different institutions, services, organizations, and also individual human being, its closest surroundings, local and central authorities.